The impact of gut microbial signals on hematopoietic stem cells and the bone marrow microenvironment - Liu, Xiru; Zhang, Hao; Shi, Guolin; Zheng, Xinmin; Chang, Jing; Lin, Quande; Tian, Zhenhao; Yang, Hui (Frontiers in Immunology, 2024)
Hematopoietic stem cells (HSCs) undergo self-renewal and differentiation in the bone marrow, which is tightly regulated by cues from the microenvironment. The gut microbiota, a dynamic community residing on the mucosal surface of vertebrates, plays a crucial role in maintaining host health. Recent evidence suggests that the gut microbiota influences HSCs differentiation by modulating the bone marrow microenvironment through microbial products. This paper comprehensively analyzes the impact of the gut microbiota on hematopoiesis and its effect on HSCs fate and differentiation by modifying the bone marrow microenvironment, including mechanical properties, inflammatory signals, bone marrow stromal cells, and metabolites. Furthermore, we discuss the involvement of the gut microbiota in the development of hematologic malignancies, such as leukemia, multiple myeloma, and lymphoma.